Misticismo patriótico en el arte republicano: Mariana de Jesús a través de la mirada de Víctor Mideros (1913-1926) [Debates] - Carrera Núñez, Luis Fernando (2020)
On the basis of paintings of the seventeenth-century saint Mariana de Jesús by the artist Víctor Mideros in the first decades of the twentieth century, the article explores the representation of religious ideals in a modern society. By analyzing these painting, as well as a pamphlet written by Archbishop Manuel María Pólit with observations on the work, a dialogue is established between the new artistic conception of the saint from Quito and the Church’s construction of its narrative about her. It also examines how Mideros broke away from colonial representations of Mariana de Jesús in the context of a renewed “millenialism” which exerted an impact on painting in the early twentieth century.